The Role of the Media in the Internet IPO Bubble - Bhattacharya, Utpal; Galpin, Neal; Ray, Rina; Yu, Xiaoyun (Journal of Financial and Quantitative Analysis, 2009)
Abstract We read all news items that came out between 1996 and 2000 on 458 Internet initial public offerings (IPOs) and a matching sample of 458 non-Internet IPOs (a total of 171,488 news items) and classify each news item as good news, neutral news, or bad news. We first document that the media were more positive for Internet IPOs in the period of the dramatic rise in share prices and more negative for Internet IPOs in the period of the dramatic fall in share prices. We then document that media hype is unable to explain the Internet bubble: A 1,646% difference exists in returns between Internet stocks and non-Internet stocks from January 1, 1997, through March 24, 2000 (the market peak), and the media can explain only 2.9% of that.